Peran Centela Asiatica Sebagai Moisturizer - Faradila, Anandita; Setyowatie, Lita (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Moisturizer is the main component of daily basic skin care especially if there is a change in the epidermal barrier and reduced water content in the epidermis layer. When the amount of water drop below 10%, the skin become dry. One of herbal plants that affect skin hydration is Centella asiatica. C. asiatica is known as Pegagan in Indonesia and belongs to the Umbelliferae/Apiaceae family. Extracts from the leaves of C. asiatica have been reported to have potential as antioxidants, antimicrobial agents, collagen synthesis agents, and even act as wound healing properties. The active components of C. asiatica include pentacyclic triterpenes, particularly asiaticoside, madecassoside, asiatic acid and madecassic acid. C. asiatica is used as an active compound in skin care preparations due to its hydrating, antioxidant, anti-inflammatory, anti-cellulite and anti-aging activities. A formulation containing a concentration of C. asiatica extract showed efficacy in increasing skin moisture by increasing the hydration state of the skin surface and reducing the occurrence of transepidermal water loss (TEWL). This literature review aims to add insight about Centella asiatica and its mechanism of action that can be used as a moisturizer for the skin. Centella asiatica can be used as a cosmetic formulation that can treat dry and sensitive skin. More research is needed to identify and determine the chemical compound C. asiatica which is responsible for various therapeutic activities, especially as an effective, safe, easy and inexpensive moisturizer.